WNT signaling represses astrogliogenesis via Ngn2‐dependent direct suppression of astrocyte gene expression. Issue 7 (19th March 2019) - Sun, Shuhui; Zhu, Xiao‐Jing; Huang, Hao; Guo, Wei; Tang, Tao; Xie, Binghua; Xu, Xiaofeng; Zhang, Zunyi; Shen, Ying; Dai, Zhong‐Min; Qiu, Mengsheng
Abstract: Neural progenitor cells (NPCs) are sequentially specified into neurons and glia during the development of central nervous system. WNT/β‐catenin signaling is known to regulate the balance between the proliferation and differentiation of NPCs during neurogenesis. However, the function of WNT/β‐catenin signaling during gliogenesis remains poorly defined. Here, we report that activation of WNT/β‐catenin signaling disrupts astrogliogenesis in the developing spinal cord. Conversely, inhibition of WNT/β‐catenin signaling leads to precocious astrogliogenesis. Further analysis reveals that activation of WNT/β‐catenin pathway results in a dramatic increase of neurogenin 2 ( Ngn2 ) expression in transgenic mice, and knockdown of Ngn2 expression in neural precursor cells can reverse the inhibitory effect of WNT/β‐catenin on astrocytic differentiation. Moreover, Ngn2 can directly bind to the promoters of several astrocyte specific genes and suppress their expression independent of STATs activity. Together, our studies provide the first in vivo evidence that WNT/β‐catenin signaling inhibits early astrogliogenesis via an Ngn2 ‐dependent transcriptional repression mechanism. Main Points: WNT/β‐catenin signaling inhibits astrogliogenesis and regulates the expression of Ngn2. Ngn2 directly suppresses the expression of astrocytic genes. Ngn2 directly suppresses the expression of astrocytic genes.